2009
DOI: 10.1002/jbm.a.32558
|View full text |Cite
|
Sign up to set email alerts
|

A systematic SPR study of human plasma protein adsorption behavior on the controlled surface packing of self‐assembled poly(ethylene oxide) triblock copolymer surfaces

Abstract: A well-controlled biocompatible nonfouling surface is significant for biomedical requirements, especially for the improvement of biocompatibility. We demonstrate the low or nonbiofouling surfaces by coating hydrophobic-hydrophilic triblock copolymers of poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) (PEO-PPO-PEO) on the CH(3)-terminated self-assembled monolayer (SAM). Two types of copolymers are used to modify the surface, one with different PEO/PPO ratios ( approximately 20/80, 40/60, and 80/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 35 publications
(50 reference statements)
2
54
0
Order By: Relevance
“…Extensive studies have also been devoted to fibrinogen adsorption on various substrates performed mostly at pH 7.4 and ionic strength of 0.15 M, pertinent to physiological conditions [14][15][16][17][18][19][20]. A variety of experimental techniques was used such as ellipsometry [14][15][16], OWLS [16], TIRF and AFM [17,18], radiolabelling [19], SPR [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive studies have also been devoted to fibrinogen adsorption on various substrates performed mostly at pH 7.4 and ionic strength of 0.15 M, pertinent to physiological conditions [14][15][16][17][18][19][20]. A variety of experimental techniques was used such as ellipsometry [14][15][16], OWLS [16], TIRF and AFM [17,18], radiolabelling [19], SPR [20].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of experimental techniques was used such as ellipsometry [14][15][16], OWLS [16], TIRF and AFM [17,18], radiolabelling [19], SPR [20].…”
Section: Introductionmentioning
confidence: 99%
“…These hydrophilic properties can be brought by poly(ethylene oxide) (PEO)-or poly(ethylene glycol) (PEG)-based materials, the most commonly used biofouling-resistant materials, earlier used in numerous studies to design anti-biofouling surfaces [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…This meant that the solidliquid adhesion energy could be affected by simply modifying the VIPS testing conditions and the solvent composition. Usually, to improve membranes' hydrophilicity, an amphiphilic copolymer is used [32,33] or a change of process performed [30]. Here, it is clearly shown that the wetting of membranes is affected by physical effects owed to a change of testing parameters.…”
Section: Microscopic Characterization Of the Pvdf Membranesmentioning
confidence: 97%